Specificity and Problems of Development of Gifted Children in Primary School Age - Shumakova N.B. (Психолого-педагогические исследования, 2018)
The article considers the features of intellectual and personal development of gifted children, problems that arise in the younger school age. The most common difficulties of the intellectually gifted first-graders, connected with the instruction in the school and the interrelations with their peers are pointed. The origins of these problems are clarified - the specifics of development in preschool childhood, and not quite adequate conditions of family upbringing and education. The value of creative or research instruction for the gifted children is revealed. The experience of realization the special interdisciplinary curriculum “Gifted Child” for gifted children based on the principles of systematic, activity, value of creation, novelty, problem finding, multimodality, personal interest, dialogical and independence are analyzed. These basic principles of formation of education allow the child to maintain the research position and develop the creative potential.